The impact of human resource competencies of front line employees on tourist arrivals of unclassified hotels in Western province, Sri Lanka - H. M. S. V. SILVA; R. A. I. MADUSHANI (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The primary goal of this research is to analyze how the Human Resource (HR) competencies of frontline employees at unclassified hotels in Sri Lanka’s western province affect the number of foreign visitors to those establishments.Methodology: 131 frontline workers were selected as possible respondents after a thorough conceptual model was developed and tested on a survey strategy.Findings: According to the research, unclassified hotels in Sri Lanka’s western province benefit greatly from the HR competencies of their frontline employees. The only significant dimensions of HR competencies were interpersonal and communication skills. The five unclassified hotels in Sri Lanka’s western province are the only ones covered by this study, which was conducted solely on a cross-sectional basis.Implications/Novelty: The study has shown that managers need to put more effort into improving the interpersonal and communication skills of their frontline workers if they want to increase the number of tourists they bring in. It has also shown that managers must assess their frontline workers’ skills to see where they need to improve.